Effects of location and crushing Ralgro implants on cattle performance (summary of three trials) - Corah, L.R.; Plegge, S.D.; Francis, G. (Kansas State University. Agricultural Experiment Station, 2011)
Implanting at an alternate location (in the muscle or fat pad at the base of the ear) or crushing the pellets did not appear to cause side effects or adversely affect animal performance. However, implanting at the alternate location significantly improved (6.6%) average daily gain in all three trials. Based on these and other studies, the recommended location for Ralgro implants is as close to the base of the ear as possible.
Keywords: Beef; Implants; Performance; Average daily gain